A comparison between the performance of DWT and LWT in image watermarking - Dujan B. Taha; Taha Basheer Taha; Najla Badie Al Dabagh (Institute of Advanced Engineering and Science, 2020)
Image watermarking algorithms can be implemented using time domain or frequency domain-based algorithms. Frequency domain watermarking produces watermarks with higher robustness; hence, many attempts have been proposed in literature using different transformations as DCT, SVD, and DWT. DWT was widely used for many reasons as its spatio-temporal feature, in which the alteration of certain portion will affect only the affected portion. In this paper an experimental comparison between the traditional DWT and the second generation of wavelet which is LWT is initiated. The experimental tests evaluated the performance of both transforms in terms of image quality and watermark robustness.